An Evaluation Of The Effectiveness Of Using The Self-Registration Station (ADM) Method At The Community Health Center, Batugana District North Padang Lawas - S. Shelly Hazlina Hararap; Ermi Girsang; Sri Lestari Ramadhani Nasution; Liani Br Ginting (Sean Institute, 2024)
Queues arise due to the need for services exceeding the capacity of services or service facilities so that users of facilities cannot immediately get services due to busy services. Very long queues and taking too long to get a turn for service are very dissatisfying for patients with the Self-Registration Kiosk (ADM) method at Batugana Health Center aims to maximize the outpatient registration process in order to create easy, fast and comfortable services for patients. However, in its implementation there are still many elderly people who do not understand its use and sometimes there are problems with the system, thus slowing down the service process at Batugana Health Center. The purpose of this study was to evaluate the effectiveness of the use of the Self-Registration Kiosk Method (ADM) at Batugana Health Center. The method in this study is qualitative analytic. The sample in this study consisted of 4 informants including: Head of the Health Center, Head of the Self-Registration Kiosk Division, Self-Registration Kiosk Officers and Outpatients. Data were obtained through in-depth interviews with informants, then the data was analyzed by data reduction through Data Triangulation and sources, then displayed in narrative form. The results of the study showed that there was an influence of human resources, SOPs and facilities and infrastructure on the use of the Self-Registration Kiosk (ADM) method at Batugana Health Center on the evaluation of the effectiveness of the use of the Self-Registration Kiosk (ADM) Method at Batugana Health Center., has not fully implemented the use of APM effectively because the expected results have not been in accordance, namely creating fast service. At Batugana Health Center, the efforts that will be made are to re-evaluate the performance of officers on APM, determine officers who really understand the APM machine. And what will be done is to create an SOP on the use of the APM machine, check the function of the APM machine, add internet quality and add electric generators.